Brand and Country of Origin Towards Consumer Attitudes in Choosing Smartphones - Apia Septira, Ika; Nur Kholiza, Heni; Rahmadhania, Rahmadhania (Manunggal Halim Jaya, 2024)
As technology advances, smartphone devices become a fascinating topic for conversation. The growth of multiple smartphone brands as choices appears to be inextricably linked to the relevance of customer attitudes in deciding which smartphone to use. The growth of multiple smartphone brands as choices appears to be inextricably linked to the relevance of customer attitudes in deciding which smartphone to use. Furthermore, when choosing a smartphone, shoppers consider the product's nation of origin. This study uses a quantitative approach method. Involving the 100-person Dumai City community. The findings of the partial analysis indicate that brands have a positive and significant effect on consumer attitudes and country of origin variables have a positive but not significant effect on consumer attitudes. Brand and country of origin together have a positive and significant effect on consumer attitudes in the Dumai City community. The result of the Determination Coefficient is 21.3%, with the remaining 78.7% impacted by other variables.